COMPETENCY-BASED TRAINING EDUCATIONAL MODEL FOR IMPLEMENTING THE RECEIPT OF WAKAF PROPERTY FOR STUDENTS AT THE INDONESIAN WAKAF BOARD - Sigit Indra Prianto; Endin Mujahidin; Budi Handrianto; Emmy Hamidiyah (Penerbit Lafadz Jaya, 2023)
The Indonesian Waqf Board in collaboration with the Sultan Maulana Hasanuddin Benten State Islamic University has carried out training and competency certification for the implementation scheme for receiving waqf assets. There were 52 students who participated in the assessment from the sharia economics department. This research method is qualitative with an observation and literature study approach as well as direct participation. Training materials are provided for competency units for the implementation scheme for receiving waqf assets, such as: (1) Managing Wakif Loyalty, (2) Implementing Acceptance of Waqf Assets, (3) Managing Wakif Complaints, (4) Marketing the waqf program, (5) Evaluating receipt of assets waqf objects, (6) Managing reputation risk. The results of the competency test on 52 assessees stated that all of them passed competently. Researchers formulate proposals for improving the competency-based training implementation model for the implementation scheme for receiving waqf assets based on the meaning of Surah Al-Baqarah Verses 246-252. First, the pattern and requirements for recruiting training participants must have criteria such as having sincere intentions, having a trustworthy nature, motivation to carry out Allah SWT's commands, having a strong physique, understanding fundraising strategies and knowledge and the participant's track record must be clear. Second, the curriculum must emphasize aspects of cultivating adab or character, including: having criteria such as consistently carrying out orders, being intelligent and having good knowledge, mastering the problems faced, not being greedy and using one's rights according to one's portion. Third, the curriculum aspect must also emphasize mental formation and strengthening by emphasizing the formation of a disciplined attitude, having good vision and leadership, having a cohesive mentality (one) with colleagues, obeying the regulations that have been set, both formal legal rules and laws and sharia principles.